2011
DOI: 10.1029/2010jd014741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of satellite-retrieved extreme precipitation rates across the central United States

Abstract: Water resources management, forecasting, and decision making require reliable estimates of precipitation. Extreme precipitation events are of particular importance because of their severe impact on the economy, the environment, and the society. In recent years, the emergence of various satellite‐retrieved precipitation products with high spatial resolutions and global coverage have resulted in new sources of uninterrupted precipitation estimates. However, satellite‐based estimates are not well integrated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
190
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(201 citation statements)
references
References 35 publications
10
190
0
1
Order By: Relevance
“…Narayanan et al [30] validated TRMM 3B42 data with India Meteorological Department (IMD) rain gauges data and showed that the satellite algorithm does not pick up very high and very low daily rainfalls. Similar perspectives were also shown in research by Tian et al [31], AghaKouchak et al [32] and Sorooshian [33]. However, many researchers also show that the TRMM data performed perfectly at monthly or a longer time scale.…”
Section: Introductionsupporting
confidence: 57%
“…Narayanan et al [30] validated TRMM 3B42 data with India Meteorological Department (IMD) rain gauges data and showed that the satellite algorithm does not pick up very high and very low daily rainfalls. Similar perspectives were also shown in research by Tian et al [31], AghaKouchak et al [32] and Sorooshian [33]. However, many researchers also show that the TRMM data performed perfectly at monthly or a longer time scale.…”
Section: Introductionsupporting
confidence: 57%
“…Moreover, in some areas, such as mountainous regions, the quality of radar datasets is not high due to beam blockage, propagation errors, and vertical variability of reflectivity. On the other hand, radar data can be obtained from only limited areas [2,7,8]. However, precipitation data extracted from satellites overcome the previous problems, giving us a chance to acquire abundant precipitation information [9].…”
Section: Introductionmentioning
confidence: 99%
“…The results of [12] showed that CMORPH and PERSIANN rainfall products indicated better precipitation estimates. However, the false alarm ratio (FAR) and volume of CMORPH and PERSIANN data sets are higher than those of TMPA-RT and TMPA-V6.…”
mentioning
confidence: 89%
“…However, the false alarm ratio (FAR) and volume of CMORPH and PERSIANN data sets are higher than those of TMPA-RT and TMPA-V6. According to [12], no single rainfall product can be considered perfect for detecting extreme precipitation events. [13] showed that at seasonal or annual time scales, CMORPH has much higher biases and RMS errors than TRMM 3B42.…”
mentioning
confidence: 99%